Conformationally rigid aromatic amino acids as potential building blocks for abiotic foldamers - Ramesh, Veera V. E.; Roy, Arup; Vijayadas, Kuruppanthara N.; Kendhale, Amol M.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes the development of conformationally constrained unnatural aromatic amino acids, constructed on rigid backbone wherein the carboxyl and amino groups project in two dimensions (planes) on the aromatic framework. Such a feature offers the possibility of design and development of conformationally ordered synthetic oligomers with intriguing structural architectures distinct from those classically observed. Furthermore, such amino acids will have the potential to extend the conformational space available for foldamer design with diverse backbone conformation and structural architectures.

Carbohydrate-derived conformationally restricted bicyclic dipeptides as potential hetero foldamer building blocks - Ramesh, Veera V. E.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Tetrahedron-Asymmetry, 2012)
Starting from carbohydrate precursors, hetero foldamer building blocks featuring diverse amino acid side chains and stereochemistry have been accessed via a multi-step synthetic protocol. These conformationally restricted bicyclic dipeptide building blocks are characterized by a constrained beta-lactam ring fused with a pyrrolidine ring carrying a hydroxyethylamine isostere (HEA) on the backbone. These building blocks offer the possibility of developing foldamers with interesting structural architectures, conspicuously different from those classically observed. Furthermore, such hetero-building blocks have the potential to augment the conformational space available for foldamer design with diverse backbone conformations and structural architectures. (C) 2012 Elsevier Ltd. All rights reserved.

Carboxamide versus sulfonamide in peptide backbone folding: a case study with a hetero foldamer - Ramesh, Veera V. E.; Kale, Sangram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic Letters, 2013)
Strikingly dissimilar hydrogen-bonding patterns have been observed for two sets of closely similar hetero foldamers containing carboxamide and sulfonamides at regular intervals. Although both foldamers maintain conformational ordering, the hydrogen-bonding pattern and backbone helical handedness differ diametrically.